Using styrofoam media to improve student learning outcomes in class IV - Hadi Suhendro; Widiya Puji Astuti; Erni Tresnawati (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The learning process carried out does not use learning media, so students only imagine the explanation given by the teacher without any media that can be observed directly by students. The aim of this research is to improve student learning outcomes. Meanwhile, the benefit of this research is to add new references regarding the use of learning media and make students happy in learning. The method used in this research is a quantitative method. The research subjects were 25 class IV students, consisting of 15 male students and 10 female students. The research results showed that there was an increase in learning outcomes with the class average reaching 85.2. In this study the subject only focused on one class, of course this does not describe the actual situation. For further research, it is recommended to take more samples to get more objective results.